Socio-psychological factors of family stability in Uzbekistan - Rabimovna, Atoyeva G ulshoda; Shokirovich, Urunov Aziz (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the problems aimed at studying the state of social-psychological factors affecting family stability in Uzbekistan the practical work carried out in this area and their scientific justification.